2021
DOI: 10.1186/s12889-021-11892-5
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and substance misuse in young people in India: results from the multisite cVEDA cohort

Abstract: Background Adverse childhood experiences (ACEs) increases vulnerability to externalising disorders such as substance misuse. The study aims to determine the prevalence of ACEs and its association with substance misuse. Methods Data from the Consortium on Vulnerability to Externalising Disorders and Addictions (cVEDA) in India was used (n = 9010). ACEs were evaluated using the World Health Organisation (WHO) Adverse Childhood Experiences Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 57 publications
0
26
1
Order By: Relevance
“…Table 4 [37,46,[110][111][112][113][114] illustrates examples of substance abuse connected to ACE. Given the knowledge that this is a significant risk, preventative measures that include the microbiome and protection against dysbiosis not only reduce the risk of substance abuse, but also canaid in protection against impediments to withdrawal.…”
Section: Substance Misuse/abusementioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 [37,46,[110][111][112][113][114] illustrates examples of substance abuse connected to ACE. Given the knowledge that this is a significant risk, preventative measures that include the microbiome and protection against dysbiosis not only reduce the risk of substance abuse, but also canaid in protection against impediments to withdrawal.…”
Section: Substance Misuse/abusementioning
confidence: 99%
“…[110] Substance misuse Meta-analysis; A study of misuse in young people found that ACE can drive male misuse of tobacco. [111] Substance abuse A study using data from the 2016-2019 National Survey of Children's Health; During childhood; Seven ACEs were included (but not child maltreatment). [46] Problematic alcohol and/or tobacco use A longitudinal study of 1179 youths of Lain American origin or descent.…”
Section: Outcome Details Referencementioning
confidence: 99%
“…The childhood years, from prenatal to late adolescence and early adulthood, are “building block” years for the basis of intelligence and skill development, self-motivation, social behavior, health and adult relationships, which extend into adulthood [ 1 , 2 ]. Some level of stress and adversity is a normal part of healthy human development.…”
Section: Introductionmentioning
confidence: 99%
“…According to the report of Centers for Disease Control and Prevention (CDC), nearly 62% of adults from the United States of America experienced atleast one type of ACE before the age of 18, and about one in six reported that they had experienced more than three types of ACEs [ 1 ]. A study from India done by Fernandes et al (2021) reported that one in two young people has child mistreatment ACEs and family-level ACEs [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Every drug has different effects on the health of one person to another. Substance abuse and its associated effects are increasing across different countries and populations, especially the youthful population in low, middle-income and developed countries (Fernandes, Spiers, Vaidya, Zhang, Sharma, Holla & Benegal, 2021). In 2022, almost 35% of school-going children were said to have used substances and drugs.…”
Section: Introductionmentioning
confidence: 99%